Stigma Negatif pada Ibu dengan Anak Gizi Buruk: Studi Fenomenologi - Erni Setiyowati (Politeknik Kesehatan Tanjung Karang, 2017)
Fulfillment the child’s nutrients is a challenge for the mother. The problem in fulfillment of nutrient can cause the children have malnutrition. The aims of this research to explore the mother experience for treating the child in malnutrition. The research used qualitative design with descriptive phenomenology approach and involved eight participants. One of the themes found from the result of the research is the unpleasant treatment during the mother treating her child. This unpleasant treatment is generally in form of oral from a health worker. This condition causes the mother reluctant to take her child to solve the problem of nutrients that occur. The mother only take their children to the health care if they have comorbidities. This condition requires the health workers to develop counseling and mentoring skill for mothers who have children with malnutrition.